2004
DOI: 10.4049/jimmunol.172.7.4018
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Targeting of the CC Chemokine Ligand 5 Results in Diminished Leukocyte Infiltration into the Central Nervous System and Reduced Neurologic Disease in a Viral Model of Multiple Sclerosis

Abstract: Intracerebral infection of mice with mouse hepatitis virus, a member of the Coronaviridae family, reproducibly results in an acute encephalomyelitis that progresses to a chronic demyelinating disease. The ensuing neuropathology during the chronic stage of disease is primarily immune mediated and similar to that of the human demyelinating disease multiple sclerosis. Secretion of chemokines within the CNS signals the infiltration of leukocytes, which results in destruction of white matter and neurological impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 53 publications
(81 reference statements)
3
111
1
Order By: Relevance
“…It may be that the Abs did not access the critical CNS compartment to achieve effect, or that Ab levels were insufficient to block chemokine effects in our system. Other studies have used these same reagents to influence CNS inflammatory events (35,36), but in different model systems. Alternatively, it may simply be that CXCL10 and CCL5 are not the critical mediators driving CNS T cell entry in response to IFN-␥ and Ptx, despite their clear up-regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be that the Abs did not access the critical CNS compartment to achieve effect, or that Ab levels were insufficient to block chemokine effects in our system. Other studies have used these same reagents to influence CNS inflammatory events (35,36), but in different model systems. Alternatively, it may simply be that CXCL10 and CCL5 are not the critical mediators driving CNS T cell entry in response to IFN-␥ and Ptx, despite their clear up-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…for 5 days following administration of AdIFN␥ and Ptx. Efficacy of these reagents has been validated in studies involving blocking of chemokine-driven immune events in mouse CNS inflammation (35,36). In neither case did the blocking Ab affect infiltration of CD45 high leukocytes, as assessed by flow cytometry (data not shown).…”
Section: Ifn-␥-induced Chemokines Plus Peripheral Ptx Promote T Cell mentioning
confidence: 99%
See 1 more Smart Citation
“…5B). Previous studies have indicated that T cell secretion of the macrophage chemoattractant CCL5 can contribute to demyelination [14,22]. Therefore, CCL5 expression and macrophage accumulation within the CNS were evaluated following CXCR3 neutralization.…”
Section: Functional Significance Of Cxcr3 During Chronic Diseasementioning
confidence: 99%
“…During both acute and chronic MHV infection, chemokines and chemokine receptors are expressed within the CNS, influencing host defense as well as disease by regulating inflammation within the CNS [9,14,[18][19][20][21][22][23]. Studies from our laboratory have clearly demonstrated important roles for CXCR3 ligands during both acute and chronic MHV infection of C57BL/6 mice [18,19,23].…”
Section: Introductionmentioning
confidence: 99%